Principles of space-time adaptive processing - Klemm, Richard (London, United Kingdom Institution of Engineering and Technology, 2006)
This third edition of Principles of Space-Time Adaptive Processing provides a detailed introduction to the fundamentals of space-time adaptive processing, with emphasis on clutter suppression in airborne and spacebased phased array radar, covering specifically the principles of airborne or spacebased MTI radar for detection of slow moving targets for use in the fields of earth observation, surveillance and reconnaissance, with special attention paid to clutter rejection techniques. The book includes topics such as signal processing, clutter models, array processing, bandwidth effects, nonlinear antenna arrays, and anti-jamming techniques, adaptive monopulse, bistatic radar configurations, SAR, ISAR and sonar.
Electronic reproduction.
Keywords: Moving target indicator radar; Adaptive signal processing; Adaptive antennas; Radar; Sonar; Electronic books